Run and hide - Brown, Don, 1949- (Clarion Books, HarperAlley, imprints of HarperCollinsPublishers, 2023)
In the tightening grip of Hitler's power, towns, cities, and ghettoes were emptied of Jews. Unless they could escape, Jewish children would not be spared their deadly fate in the Holocaust, a tragedy of unfathomable depth. Only 11% of the Jewish children living in Europe before 1939 survived the Second World War. Run and Hide tells the stories of these children, forced to leave their homes and families, as they escaped certain horror. Some children flee to England by train. Others are hidden from Nazis, sometimes in plain sight. Some are secreted away in attics and farmhouses. Still others make miraculous escapes, cresting over the snow-covered Pyrenees mountains to safety.